Marxism and medieval studies Marxist historiography in East Central Europe - Nodl, Martin 1968-; Węcowski, Piotr 1972- (Brill, 2024)
"This volume is a unique publication as it examines the Marxist attitudes in East Central European historiography and archaeology for the first time, with an emphasis on the co-existence of Marxist and other methodologies between the 1950s and 1970s in the local historiographies in question. Its approach is to distinguish between pseudo-Marxism as an ideological tool on the one hand, and Marxism in the form of historical materialism as a way to interpret the medieval world on the other. Contributors are: Florin Curta, Piotr Guzowski, Adam Hudek, Tereza Johanidesová, Jitka Komendová, Jiří Macháček, Andrzej Marzec, Martin Nodl, Attila Pók, David Radek, Tadeusz Paweł Rutkowski, Iurie Stamati, Rafał Stobiecki, Gábor Thoroczkay, Przemysław Wiszewski, Piotr Węcowski, Martin Wihoda, and Dušan Zupka"--
"The book Marxism and Medieval Studies: Marxist Historiography in East Central Europe originated at a workshop, which took place on 25 October 2019 and in which the Centre of Medieval Studies, Institute of Philosophy of the CAS, v. v. i., Institute of Contemporary History of the CAS, v. v. i., and Uniwersytet Warszawski participated within the Strategy AV 21 programme. The common denominator of the presented studies is Marxism and its influence on historical thought in the Czech and Polish milieux of the second half of the 20th century. The original publication of the conference proceedings in Czech and Polish included only Czech and Polish contributors. The present English manuscript was expanded with chapters reflecting the work of Slovak, Hungarian, Romanian, and Yugoslav scholars."-- Introduction. - Includes index
Keywords: Geschichte 1950-1980; Middle Ages / Historiography; Marxian historiography; Moyen Âge / Historiographie; Historiographie marxiste; Mediävistik; Marxismus; Ostmitteleuropa; Aufsatzsammlung